Alternate wetting and drying (AWD) in Africa - CGIAR Research Program on Rice (2020)
Using a participatory approach, AWD has been successfully validated in three climatic zones in West Africa: semi-arid (Senegal River Valley in Senegal and Plain of Zoungou and Valley of Sourou in Burkina Faso), sub-humid dry (Kou valley and plain of Karfiguela in Burkina Faso) and sub-humid humid (Côte d’Ivoire).